Enhancing Motorcycle Riding Safety through Smart Helmet Design Using the Quality Function Deployment (QFD) Approach - Febrian Krisnawati; Lutfi Hidayat (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2026)
Motorcycles dominate daily transportation in Indonesia, which contributes to a substantial number of traffic accidents involving motorcyclists. Despite regulations requiring helmet use, head injuries continue to occur frequently, largely due to improper fastening of helmet chin straps. This research focuses on the development of a smart helmet that emphasizes safety quality through the implementation of an automatic chin strap locking mechanism using a quality management perspective. The Quality Function Deployment (QFD) method is employed to systematically convert user expectations into relevant technical design specifications. Primary data were obtained through questionnaires to identify the voice of customer concerning safety, comfort, usability, design preferences, and price considerations. Data quality was ensured through validity and reliability testing prior to analysis. The findings reveal that safety-oriented features, especially the automatic chin strap locking system and warning alarm, represent the most critical factors in enhancing riding safety quality. The proposed smart helmet design successfully combines key safety features with user comfort and ease of use. This study confirms that QFD is a suitable approach for developing user-centered, safety-focused products and offers practical insights for smart helmet design within the industrial engineering field.